IN PURSUIT OF QUALITY BY VIABLE QUALITY ASSURANCE SYSTEM: THE CONTROLLERS’ PERCEPTIONS - Aziz, Anwar (Journal of Ayub Medical College Abbottabad, 2011)
Background: Patients, families and communities expect safe, competent and compassionate nursing care that has always been a core value of nursing. To meet these expectations, a valid and reliable quality assurance (QA) system is crucial to ensure that nurse-graduates are competent, confident and fit to practice. The QA approach is seen to be fundamental for quality improvement, it would be appropriate to consider its influence in the nursing education in Pakistan as the current situation is evident of non-existence of such a system to assure its quality Method: The data is drawn from a qualitative case study conducted in 2004. Among a purposive sample of 71 nurses inclusive of a group of Controllers were interviewed on one-to-one basis. Interviews were audio taped to reduce the risk of any misinterpretation and to facilitate the exact description of data as it was said. The non-directive, semi-structured and open-ended questionnaire was used to collect data. Thematic analysis of verbatim transcripts of the interviews was done. Results: The study findings reveal a unanimous desire of the nurses to gauge quality of nurse education through efficient and effective quality assurance system. Conclusion: A crucial need is felt to develop a viable quality assurance system to ensure approved level of quality in nursing education to deliver the right care to the right patient at the right time, every time. The continuous quality assurance and improvement (CQAI) framework based on Deming Quality Cycle (Plan, Do, Check and Act) could facilitate appropriate designing and development of mechanism. Keywords: Quality, Quality Assurance, Nursing Education, Controllers, Continuous Quality Improvement Framework, Nursing Council